Development of convenient quality control analysis method and improvement on the radiochemical yield using F-18-Labelled choline - Hassan, Muhammad Hishar (2016)
Prostate cancer continues to be the most prevalent cancer in men in Malaysia. It is anticipated that the number of prostate cancer sufferers’ will increase in future. In the case of Positron Emission Tomography / Computed Tomography (PET/CT), clinicians cannot solely rely on F-18 Fluorodeoxyglucose (F-18 FDG) as there were few studies demonstrated the use of F-18 FDG was pointless in prostate cancer imaging. Thus, this current study presents development of convenient quality control analysis method and improvement performed on the azeotropic drying of no-carrier-added (n.c.a.) F-18 Fluorine to increase the F-18 Fluorocholine (F-18 FCH) radiochemical yield. From these studies, a convenient, efficient and reliable method for quality control analysis of F-18 FCH was successfully developed and validated to comply all the release criteria even in a limited equipment set-up. As most of the equipment set-up in the quality control laboratory in the present study was meant for the routine quality control analysis of F-18 FDG, several parameters were changed in order to adapt to the F-18 FCH quality control method without affecting the routine quality control analysis of F-18 FDG. The synthesis of F-18 FCH was successfully performed on a commercial synthesis module, GE TracerLab MxFDG with fairly good radiochemical yields, between 5 to 15%, which decay is not corrected. Interestingly, the finding from this study shows the potential of improvement on the azeotropic drying condition of n.c.a F-18 Fluorine as a preferred technique to improve the radiochemical yield of F-18 FCH.